Implementation of Polmas by the Binmas Unit in Preventing Criminal Acts of Domestic Violence in the Kuningan Polres Area - Paramaswara, Rama (Police Studies Review, 2024)
Crimes in domestic violence that occurred in the Kuningan police area became a crime with a high number in the last 3 years, and the number of resolutions of criminal acts tends to fluctuate. There is a preventive effort undertaken by the Kuningan Police Chief to prevent domestic violence through Polmas through dialogical patrols. The purpose of this study is to identify the implementation of Community Policing conducted by Satan Binmas Kuningan Police in preventing domestic violence. In addition, it also identifies the factors that influence the implementation of Community Policing conducted by the Binmas Unit towards the prevention of criminal acts against domestic violence. Theories used in this research are management theory, and competency theory. The concept used is the concept of community policing, the concept of prevention, the concept of domestic violence, the concept of cooperation, and the concept of dialogical patrol which is used to study the implementation of community policing by the Community Policing Binmas Unit in preventing domestic violence. This research uses a qualitative approach with descriptive methods. Data sources include primary data sources and secondary data sources. Data collection techniques used were interviews, observation, and study of documents. The data analysis used includes data reduction, data display and conclusion drawing. Based on the results of the study concluded that the implementation of Community Policing by the Kuningan Police Binmas Unit has not been going well. There are several factors that influence, namely the factors that support and also inhibiting the implementation of Community Policing to prevent domestic violence committed by the Kuningan Police Binmas Unit. The advice given is to empower members outside the Community Binmas Unit as community police officers. In compiling Kamtibmas material or messages regarding domestic violence involving experts in their fields. Providing understanding in the form of self-empowering to women in Kuningan Regency.